A Decision To Pay Zakat On Zakat Management Organizations: Factors Of E-Promotion And E-Service Quality - Najmudin, Najmudin; Syihabudin, Syihabudin; Ma'zumi, Ma'zumi; Suja'i, Suja'i; Maelani, Puspita; Aziz, Abdul (FEB Universitas Sultan Ageng Tirtayasa, 2023)
This study aims to determine 1. The effect of e-promotion on the decision to pay zakat in zakat management organizations, 2. The effect of e-service quality on the decision to pay zakat in zakat management organizations, And 3. The effect of e-promotion and e-service quality on the decision to pay zakat in zakat management organizations. The object of this research is the Muzakki who have paid zakat to zakat management organizations both LAZ and BAZNAS, Banten Province, with 96 respondents. The research method used is quantitative. Methods of data collection using a questionnaire. Data were analyzed using a multiple linear regression test. The results of this study indicate that (1). E-Promotion significantly and positively effects decision to pay zakat in zakat management organizations. 2. E-Service quality significantly and positively effects decision to pay zakat in zakat management organizations, And 3. E-Promotion and E-Service Quality simultaneously have a positive and significant effect on the decision to pay zakat in zakat management organizations. The total contribution effect of e-promotion and e-service quality to the decision to pay zakat is 21 percent, while the remaining 79 percent is effected by other factors not examined in this study.